Mammalian Cell Cultures for Biologics Manufacturing - Zhou, Weichang; Kantardjieff, Anne.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Anne Kantardjieff and Weichang Zhou Mammalian Cell Cultures for Biologics Manufacturing Scott Estes and Mark Melville Mammalian Cell Line Developments in Speed and Efficiency Susan Abu-Absi, Sen Xu, Hugh Graham, Nimish Dalal, Marcus Boyer and Kedar Dave Cell Culture Process Operations for Recombinant Protein Production Sadettin S. Ozturk Equipment for Large-Scale Mammalian Cell Culture Daniel M. Marasco, Jinxin Gao, Kristi Griffiths, Christopher Froggatt, Tongtong Wang and Gan Wei Development and Characterization of a Cell Culture Manufacturing Process Using Quality by Design (QbD) Principles Michael J. Gramer Product Quality Considerations for Mammalian Cell Culture Process Development and Manufacturing Dayue Chen Safety Assurance for Biologics Manufactured in Mammalian Cell Cultures: A Multitiered Strategy Dawn M. Ecker and Thomas C. Ransohoff Mammalian Cell Culture Capacity for Biopharmaceutical Manufacturing Karthik P. Jayapal and Chetan T. Goudar Transcriptomics as a Tool for Assessing the Scalability of Mammalian Cell Perfusion Systems Enda Moran and Patrick Gammell Lifecycle Management for Recombinant Protein Production Using Mammalian Cell Culture Technology
Mammalian Cell Cultures for Biologics Manufacturing -- Mammalian Cell Line Developments in Speed and Efficiency -- Cell Culture Process Operations for Recombinant Protein Production -- Equipment for Large-Scale Mammalian Cell Culture -- Development and Characterization of a Cell Culture Manufacturing Process Using Quality by Design (QbD) Principles -- Product Quality Considerations for Mammalian Cell Culture Process Development and Manufacturing -- Safety Assurance for Biologics Manufactured in Mammalian Cell Cultures: A Multitiered Strategy -- Mammalian Cell Culture Capacity for Biopharmaceutical Manufacturing -- Transcriptomics as a Tool for Assessing the Scalability of Mammalian Cell Perfusion Systems -- Lifecycle Management for Recombinant Protein Production Using Mammalian Cell Culture Technology.
Keywords: Chemistry; Pharmaceutical technology; Biotechnology; Cell culture; Chemistry; Biotechnology; Cell Culture; Pharmaceutical Sciences/Technology.